A plug-and-play platform of ratiometric bioluminescent sensors for homogeneous immunoassays - Yan Ni (Nature Portfolio, 2021)
Many current immunoassays require multiple washing, incubation and optimization steps. Here the authors present Ratiometric Plug-and-Play Immunodiagnostics (RAPPID), a generic assay platform that uses ratiometric bioluminescent detection to allow sandwich immunoassays to be performed directly in solution.